2006
DOI: 10.1038/sj.ijo.0803520
|View full text |Cite
|
Sign up to set email alerts
|

Weight cycling during growth and beyond as a risk factor for later cardiovascular diseases: the ‘repeated overshoot’ theory

Abstract: In people trying to lose weight, there are often repeated cycles of weight loss and regain. Weight cycling is, however, not limited to obese adults but affects people of normal weight, particularly young women, who are unhappy with their appearance. Furthermore, the onset of a pattern of weight cycling is shifting towards younger ages, owing to the increasing prevalence of overweight and obesity in children and adolescents, and the pressure from the media and society for a slim image even for normal weight chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
95
3
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 88 publications
(93 reference statements)
5
95
3
6
Order By: Relevance
“…This contention is in line with prospective studies indicating more consistent association with increased risks for major weight gain in initially normal-weight subjects than in initially overweight and obese subjects attempting to lose weight (16,24) . With the prevalence of dieting increasing among individuals in the normal-weight range (due to pressure for a slim image, body dissatisfaction or athletic performance) and accumulating evidence suggesting increased cardiometabolic risks associated with weight fluctuations in the non-obese population groups (4,63) , the notion that dieting makes some fatter warrants greater experimental scrutiny and deserves greater public health concern than so far acknowledged.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This contention is in line with prospective studies indicating more consistent association with increased risks for major weight gain in initially normal-weight subjects than in initially overweight and obese subjects attempting to lose weight (16,24) . With the prevalence of dieting increasing among individuals in the normal-weight range (due to pressure for a slim image, body dissatisfaction or athletic performance) and accumulating evidence suggesting increased cardiometabolic risks associated with weight fluctuations in the non-obese population groups (4,63) , the notion that dieting makes some fatter warrants greater experimental scrutiny and deserves greater public health concern than so far acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these failures, national surveys in Europe and North America indicate that 30-50 % women and 10-30 % men are currently or have recently attempted dieting to lose weight (5)(6)(7) . With studies of the long-term outcomes of energy-restricting diets showing that at least one-third of dieters regain more weight than they lost (8) , together with population groups as diverse as obese and lean, young and old, sedentary and athletes attempting to lose weight on some form of diet therapy (4,5) , there is concern as to whether dieting may paradoxically be promoting exactly the opposite of what it is intended to achieve. To put it bluntly, does dieting make people fatter as proposed nearly three decades ago by Cannon and Einzig (9) in a book entitled Dieting makes you fat.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Although there is a general agreement that modest weight loss has beneficial health effects in obese patients, 6 there are some hypotheses that suggest that weight cycling could be damaging particularly for CVD risk. 7,8 However, studies investigating the effect of weight variability on CVD risk have shown controversial results. Some studies indicated that the overall weight trend had a greater deleterious effect on CVD risk than weight fluctuation (WF) (that is the WF effect was not significant after adjustment for weight change), [9][10][11] whereas others concluded that WF had an independent effect.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the considerable problems with establishing the efficacy of weight loss programs, there is the potential for iatrogenic effects of deliberate weight loss attempts. For example, evidence suggests that the weight-cycling that frequently results from repeated attempts to lose weight is itself more harmful to cardiovascular and metabolic health than maintaining a high body weight (e.g., Lissner et al, 1991;Montani et al, 2006;Strohacker & McFarlin, 2010), and that weight loss and appearance management reasons for exercise are associated with higher levels of self-objectification, disordered eating, and body dissatisfaction than are reasons based on health or enjoyment (e.g., Prichard & Tiggemann, 2005). Research also suggests that although weight loss goals may motivate initial engagement in exercise programs, these same goals can undermine sustained engagement with exercise and physical activity by promoting the conclusion that exercise is "not working" if weight loss does not occur, despite other substantial benefits to health (Robison, 2005;Teixeira, Silva, Mata, Palmeira, & Markland, 2012a).…”
Section: Weight Loss Is a Fraught Goalmentioning
confidence: 99%